1994
DOI: 10.3177/jnsv.40.201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Soybean Milk and Soybean Milk Peptide on Bone Metabolism in the Rat Model with Ovariectomized Osteoporosis.

Abstract: SummaryWe have reported that soybean milk is an excellent source for increasing bone mineral density (BMD) and mechanical bone strength. However, it is not known what kind of components in soybean milk affect bone metabolism. Consequently, the purpose of this study is to fi nd the effective components in soybean milk on bone metabolism. It might be some peptide in soybean milk. Therefore, in this study the soybean milk was separated into two different preparations according to molecular weight: a high-molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 14 publications
2
29
0
2
Order By: Relevance
“…Treatment with isoflavone extract at 6.25 g/kg appeared to prevent bone loss in the femur and lumbar vertebra. These results are supported by previous observations of the positive effects of soybean products -such as soybean protein and soy milk powder -on the bone density of female rats, 8,12,13) because these products contained genistein and daidzein. But, the effects of isoflavone on ALP and TRAP activities are not the same as that of estrogen.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Treatment with isoflavone extract at 6.25 g/kg appeared to prevent bone loss in the femur and lumbar vertebra. These results are supported by previous observations of the positive effects of soybean products -such as soybean protein and soy milk powder -on the bone density of female rats, 8,12,13) because these products contained genistein and daidzein. But, the effects of isoflavone on ALP and TRAP activities are not the same as that of estrogen.…”
Section: Discussionsupporting
confidence: 81%
“…This positive effect of soy protein on bone was ascribed to its amino acid composition. Omi et al 12) reported that female rats fed soymilk had greater bone mineral density and mechanical bone strength than did rats fed casein. The authors speculated that this beneficial effect was due to enhanced intestinal absorption of calcium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are several investigations on the effects of milk and soymilk on human and animal bones (Recker and Heaney, 1985;Omi et al, 1994; Kikuchi-Hayakawa et al, 1998). However, the results are controversy.…”
mentioning
confidence: 99%
“…Soymilk contains isoflavones, which are thought to have beneficial effects on the bone (Setchell and Lydeking-Olsen, 2003). It was reported that soymilk was effective for increasing bone mineral density (BMD) and mechanical bone strength, and enhancing intestinal calcium absorption (Omi et al, 1994). On the other hand, the action of dietary isoflavones during the premenopausal and perimenopausal periods appears to be variable.…”
mentioning
confidence: 99%